The Transformation of Arab Philanthropic Economy from Pre-Islamic to Post-Prophetic Period: A Historical-Managerial Study and Futuristic Relevance - Assalwa, Shafira Amalia; Ma'arif, Ilham Fikri (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2025)
The inequality of wealth distribution, market exploitation, and the crisis of social values in contemporary global society point to the need for an alternative value-based economic model. This study aims to examine the transformation of the Arab economic system from the exploitative pre-Islamic era to the prophetic economic model during the time of the Prophet Muhammad, characterised by justice and spiritual orientation. This research employs historical, value-based management, and futuristic approaches. Through a review of classical and contemporary literature, as well as a critical analysis of the Prophet's economic practices, it was found that the early Islamic economic system was not only grounded in revelation (the Qur'an and Sunnah) but also responsive to social reality with a humanistic and inclusive approach. The Prophet established the foundations of micro and macroeconomics based on the values of tawhid, justice, and equitable wealth distribution, as demonstrated through the prohibition of usury, market supervision, and the application of philanthropic concepts such as zakat, infaq, sadaqah, and waqf. The results indicate that prophetic economics is integrative and adaptable to changing times, serving as a prototype for a more ethical and sustainable future economic system. This finding serves as the basis for reconstructing an Islamic economic model that is relevant to contemporary global civilisation.